Facile synthesis of near-infrared bodipy by donor engineering for in vivo tumor targeted dual-modal imaging. Issue 45 (29th October 2021) - An, Feifei; Xin, Jingqi; Deng, Caiting; Tan, Xiaofang; Aras, Omer; Chen, Nandi; Zhang, Xiaohong; Ting, Richard
Abstract : The impact of donor strength on Bodipys' optical properties and its applications for tumor near-infrared fluorescence imaging and photoacoustic tomography. Abstract : Bodipy is one of the most popular dyes for bioimaging, however, a complicated synthetic protocol is needed to create and isolate ideal near-infrared (NIR) emissive Bodipy derivatives for optical bioimaging. It is noticed that the donor species impact the wavelength when the π-conjugation system of green light emissive Bodipy is elongated via a one-step reaction. Herein, several Bodipy dyes bearing different common donors are synthesized. Their optical properties confirm that both absorption and emission peaks of the synthesized Bodipy could be tuned to NIR wavelength by using stronger donors via a facile reaction. The synthesized monocarboxyl Bodipy could conjugate with aminated PEG to yield an amphiphilic polymer, which further self-assembles into a NIR nanoparticle (NP). The NIR NP exhibits preferential tumor accumulation via the enhanced permeation and retention (EPR) effect, making it useful for tumor diagnosis by both fluorescence imaging and photoacoustic tomography.